THERAPY FOR COUGH IN YOUNG CHILDREN - K.S. Volkov; E.A. Vishneva; A.A. Alekseeva; R.М. Torshkhoeva; Yu.G. Levina; A.Yu. Tomilova; M.D. Bakradze (Педиатрическая фармакология, 2010)
Cough is one of the most frequent reasons parents take their child to a doctor. Most frequently it develops against the backdrop of respiratory infections of viral, mixed viral-bacterial and bacterial aetiology. Currently the issue of applying efficient and at the same time safe medications for acute respiratory infections in young children is quite pressing. The article provides data from studies in which a complex plant drug is administered in children with respiratory infections. The results obtained indicate the efficacy of including herbal syrup in the therapy for children with acute respirator infections. The medication lowers the intensity of the cough providing a soft expectorant and spasmolytic effect, and reduces medicinal burden on the child’s system. Key words: cough, respiratory infections, children. (Pediatric Pharmacology. – 2010; 7(4):95-100)